2006
DOI: 10.1124/mol.106.028902
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Inhibits Androgen Production in NCI-H295R Cells by Regulating Gene Expression of CYP17 and HSD3B2

Abstract: Thiazolidinediones (TZDs) such as pioglitazone and rosiglitazone are widely used as insulin sensitizers in the treatment of type 2 diabetes. In diabetic women with polycystic ovary syndrome, treatment with pioglitazone or rosiglitazone improves insulin resistance and hyperandrogenism, but the mechanism by which TZDs down-regulate androgen production is unknown. Androgens are synthesized in the human gonads as well as the adrenals. We studied the regulation of androgen production by analyzing the effect of piog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 41 publications
2
47
1
Order By: Relevance
“…The decrease in CYP17 gene expression could shift direction to the production of mineralocorticoids other than androgen synthesis. Interestingly, our results correlated well with a recent study that showed a significant reduction in the basal and agonist-induced 3bHSD2 and CYP17 gene expression along with inhibited androgen biosynthesis in the H295R cells after exposure to pioglitazone (Kempná et al 2007). …”
Section: Discussionsupporting
confidence: 92%
“…The decrease in CYP17 gene expression could shift direction to the production of mineralocorticoids other than androgen synthesis. Interestingly, our results correlated well with a recent study that showed a significant reduction in the basal and agonist-induced 3bHSD2 and CYP17 gene expression along with inhibited androgen biosynthesis in the H295R cells after exposure to pioglitazone (Kempná et al 2007). …”
Section: Discussionsupporting
confidence: 92%
“…PPARγ agonists have also been shown to reverse the enhanced expression of P450c17 induced by specific inhibition of MEK/ERK in human adrenal cells [107] (Fig. 3).…”
Section: Insulin-sensitizing Drugsmentioning
confidence: 95%
“…On the other hand, specific inhibition of MEK/ERK, another component of the MAPK insulin pathway, increases P450c17 activity [105]. Increased expression of P450c17 after inhibition of MEK/ERK was also found in human adrenal cells [107]. The attenuated MEK/ERK signal could stimulate androgen production via a reduction in c-fos expression, because c-fos was shown to inhibit P450c17 expression in a thecal cell tumor model [108].…”
Section: 22mentioning
confidence: 98%
“…The luciferase reporter constructs for the genomic promoter sequences of CYP11A1, CYP17, CYP11B1, as well as the expression plasmids for b-galactosidase, have been described previously (Mueller et al, 2006(Mueller et al, , 2007Kempna et al, 2007;Atanasov et al, 2008). The reporter plasmid GRE2tk and the expression plasmid for GC receptor SVGR1 were kindly provided by Sam Okret (Karolinska Institute, Stockholm, Sweden; Pazirandeh et al, 1999).…”
Section: Plasmidsmentioning
confidence: 99%